Interview with David Rudkin - Bolfarine, Mariana (ABEI Journal, 2015)
Interview with David Rudkin on the radio play Cries from Casement as his Bones are Brought to Dublin. Medium: e-mail; date: 17/04/2012Keywords: David Rudkin; Cries from Casement as his Bones are Brought toDublin.